Implementation of Management and Network Security Using Endian UTM Firewall - Muhammad Arifin, Fikri; Andriana Mutiara, Giva; Ismail, Ismail (School of Applied Science, Telkom University, 2017)
Internet is a source of information which is widely used today. However, the mode of internet abused becomes more various and unavoidable. The internet abused can be done from external or internal networks. Unified Threat Management (UTM) is one of a good solution to secure the networks, because it has several security features such as firewall, proxy, Intrusion Prevention System (IPS) and several other security features in one package. Endian is an UTM distro which is an open source in large community. Besides having some security features, Endian also has some network management features such as DHCP, routing, and VPN. This research put Endian as the center of a network topology that connected to the internal network/LAN, DMZ Server, and Internet Network/WAN. The tests are conducted in the form of implementation of DHCP feature, content filtering, port restrictions on interzone, and the response of the IPS features that exist on the Endian while receiving the attack. The results showed that Endian UTM is quite well in maintaining the security of the networks.